Anthropocentric Proverbs in the English Picture of the World as Aspect of Linguistic Axiology (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article is devoted to the analysis and description of the problem of national and cultural specificity based on the paremiological picture of the world in the English-speaking society. The study of these concepts in the works of foreign scientists was carried out; identified and described axiological features in proverbs based on gender stereotypes in the English language, opposing masculinity and femininity. Anthropocentric proverbs demonstrate an individual's understanding of the reality around us and what is happening through the prism of himself, and also indicate the impact of language, on human behavior and thinking, the relationship between language and society, the relationship between language and spiritual culture.